PEMBELAJARAN REALISTIC MATHEMATIC EDUCATION (RME) BERBASIS KARAKTER KREATIF:UPAYA MEMPERSIAPKAN CALON GURU SD YANG UNGGUL DAN BERKARAKTER - Via Yustitia (Universitas PGRI Yogyakarta, 2016)
Mathematics is regarded as a difficult course load for students PGSD, whereas those aspiring teachers who will teach konsepMatematika in elementary school (SD).Pembelajaran mathematics in elementary directed to the formation of personality andability to think mathematics. PGSD Adi Buana University PGRI Surabaya being proactivewith one mission, which is to produce graduates who excel and character. Students have thehabit of memorizing a concept, but do not understand the concept. That is, to solve theproblems of students always solve the problems in the manner provided lecturers. Thisresulted in students not able to develop creative character. One approach to learning that isable to develop creative character is the approach Realistic Mathematics Education (RME).The paper lists different types of literature review that discusses learning RMEberbasiscreative character as an effort to prepare prospective elementary school teachers who exceland character. subjects based on the theme; removal of subjects one to the other subjects;make APE in accordance with the theme; developing materials.Keywords: Character Creative, Realistic Mathematis Education (RME).Â